44.1k views
1 vote
Which expression is equivalent to -3(2m-1)-n
6m-n-3
6m-n+3
-6m-n-3
-6m-n+3

User Kelalaka
by
6.8k points

2 Answers

0 votes
Let's simplify step-by-step.3(2m−1)−n
Distribute:= (−3)(2m)+(−3)(−1)+−n=6m + 3 + −n
Answer: D= 6m − n +3





B). -3(2m-1)-n Final result : -6m - n + 3 Step by step solution : Step 1 :Equation at the end of step 1 : (0 - 3 • (2m - 1)) - n Step 2 : Step 3 :Pulling out like terms : 3.1 Pull out like factors :

-6m - n + 3 = -1 • (6m + n - 3)
Final result : - 6m - n + 3

User Nanny
by
5.7k points
0 votes
-6m -n +3

by order of operations
-3(2m-1)-n=-6m+3-n=-6m-n+3
User Farasath
by
6.2k points